Effect of oxide flux particle size on weld bead morphology of hastelloy C-22 - Patel, Dixit; Jani, Sekutu; Shah, Darshit (Penerbit Universiti Kebangsaan Malaysia, 2022)
Activated tungsten inert gas welding (ATIG) welding is a new approach to Tungsten Inert Gas (TIG) welding that has the potential to improve weld penetration. This paper investigates the effect of micro and nanoparticle size oxide flux during TIG welding of Hastelloy C-22. The effect of SiO2 and Al2O3 oxide fluxes in terms of particle size and thermal stability on surface appearance, bead geometry, and microhardness of the fusion zone of hastelloy C-22 is investigated. The surface appearance of ATIG weld has a better appearance using nanoparticle size oxide flux when compared with the same micro size oxide flux. A slag layer produced by nano flux decomposition during TIG welding is very less compared to micro oxide fluxes. Nanoparticle SiO2 flux has the potential to improve weld penetration and depth to width (D/W) ratio in the generated weldment when compared to microparticle SiO2 flux during TIG welding Process. When nanoparticle Al2O3 is used in TIG welding, weld penetration or the D/W ratio do not increase significantly. Due to the high voltage produced at the same arc length, TIG welding with nanoparticle SiO2 flux produces a high heat input. Furthermore, higher arc temperatures produce by nanoparticle fluxes at the arc column, resulting in increased penetration depth.